Association of genetic polymorphisms of brain natriuretic peptide with cardiovascular diseases - A. Ya. Panarina; G. I. Lifshits (Российский кардиологический журнал, 2024)
Currently, natriuretic peptides (including brain natriuretic peptide (BNP)) are widely used in clinical practice as biomarkers for various cardiovascular diseases. Study of the structure and function of NPPA-NPPB locus can help to better identify patients at risk of future cardiovascular diseases, in particular heart failure.